Impact of aging on animal models of Parkinson's disease - Klæstrup, Ida Hyllen; Just, Mie Kristine; Holm, Karina Lassen; Alstrup, Aage Kristian Olsen; Romero-Ramos, Marina; Borghammer, Per; Van Den Berge, Nathalie (Frontiers in Aging Neuroscience, 2022)
Aging is the biggest risk factor for developing Parkinson's disease (PD), the second most common neurodegenerative disorder. Several animal models have been developed to explore the pathophysiology underlying neurodegeneration and the initiation and spread of alpha-synuclein-related PD pathology, and to investigate biomarkers and therapeutic strategies. However, bench-to-bedside translation of preclinical findings remains suboptimal and successful disease-modifying treatments remain to be discovered. Despite aging being the main risk factor for developing idiopathic PD, most studies employ young animals in their experimental set-up, hereby ignoring age-related cellular and molecular mechanisms at play. Consequently, studies in young animals may not be an accurate reflection of human PD, limiting translational outcomes. Recently, it has been shown that aged animals in PD research demonstrate a higher susceptibility to developing pathology and neurodegeneration, and present with a more disseminated and accelerated disease course, compared to young animals. Here we review recent advances in the investigation of the role of aging in preclinical PD research, including challenges related to aged animal models that are limiting widespread use. Overall, current findings indicate that the use of aged animals may be required to account for age-related interactions in PD pathophysiology. Thus, although the use of older animals has disadvantages, a model that better represents clinical disease within the elderly would be more beneficial in the long run, as it will increase translational value and minimize the risk of therapies failing during clinical studies. Furthermore, we provide recommendations to manage the challenges related to aged animal models.